Myotubularin-related Protein 4 (MTMR4) Attenuates BMP/Dpp Signaling by Dephosphorylation of Smad Proteins. - Yu, J.; He, X.; Chen, Y.G.; Hao, Y.; Yang, S.; Wang, L.; Pan, L.; Tang, H. (Journal of Biological Chemistry, 2013)
Bone morphogenetic proteins (BMPs) signaling essentially regulates a wide range of biological responses. Although multiple regulators at different layers of the receptor-effectors axis have been identified, the mechanisms of homeostatic BMP signaling remain vague. Herein we demonstrated that myotubularin-related protein 4 (MTMR4), a FYVE domain-containing dual-specificity protein phosphatase (DUSP), preferentially associated with and dephosphorylated the activated R-Smads in cytoplasm, which is a critical checkpoint in BMP signal transduction. Therefore, transcriptional activation by BMPs was tightly controlled by the expression level and the intrinsic phosphatase activity of MTMR4. More profoundly, ectopic expression of MTMR4 or its Drosophila homolog CG3632 genetically interacted with BMP/Dpp signaling axis in regulation of the vein development of Drosophila wings. By doing so, MTMR4 could interact with and dephosphorylate Mothers against Decapentaplegic (Mad), the sole R-Smad in Drosophila BMP pathway, and hence affected the target genes expression of Mad. In conclusion, this study has suggested that MTMR4 is a necessary negative modulator for the homeostasis of BMP/Dpp signaling.